Upper limb joint coordination preserves hand kinematics after a traumatic brachial plexus injury - Lustosa, Luiggi; Silva, Ana Elisa Lemos; Carvalho, Raquel de Paula; Vargas, Claudia D. (Frontiers in Human Neuroscience, 2022)
Background: Traumatic brachial plexus injury (TBPI) causes a sensorimotor deficit in upper limb (UL) movements. Objective: Our aim was to investigate the arm-forearm coordination of both the injured and uninjured UL of TBPI subjects. Methods: TBPI participants (n=13) and controls (n=10) matched in age, gender, and anthropometric characteristics were recruited. Kinematics from the shoulder, elbow, wrist and index finger markers were collected while upstanding participants transported a cup to mouth and returned the UL to a starting position. The UL coordination was measured through the relative phase (RP) between arm and forearm phase angles and analyzed as a function of the hand kinematics. Results: For all participants, the hand transport had a shorter time to peak velocity (p<0.01) compared to the return. Also, for the control and the uninjured TBPI UL, the RP showed a coordination pattern that favored forearm movements in the peak velocity of the transport phase (p<0.001). TBPI participants' injured UL showed a longer movement duration in comparison to controls (p<0.05), but no differences in peak velocity, time to peak velocity and trajectory length, indicating preserved hand kinematics. The RP of the injured UL revealed altered coordination in favor of arm movements compared to controls and to the uninjured UL (p<0.001). Finally, TBPI participants' uninjured UL showed altered control of arm and forearm phase angles during the deceleration of hand movements compared to controls (p<0.05). Conclusion: These results suggest that UL coordination is reorganized after a TBPI so as to preserve hand kinematics.